Open Cholecystectomy in Respiratory and Cardiovascular disease patients under Lumbar combined Spinal-Epidural Anesthesia - Haidar N. Mohammed; Ayad Ahmad Mohammed; Mohammed Abdulameer Algumrawi (Zanco Journal of Pure and Applied Sciences, 2021)
Background and Aims: Regional anesthesia gained popularity over the last three decades due to the technical advances across subdisciplines, better understanding of the physiology, the advances in the field of anesthetic drugs, and the better approach in training for such techniques. The technique is currently used in many anatomical levels and most surgical procedures can be performed using the combined spinal epidural type. The aim of this study is to evaluate the feasibility of the combined spinal-epidural anesthesia in patients with respiratory and cardiovascular diseases who underwent open cholecystectomy. Patients and methods: This prospective cross sectional study which was done on patients undergoing elective open cholecystectomy (n=119) for whom the general anesthesia was contraindicated due to major cardiovascular and pulmonary diseases, under lumber combined spinal-epidural anesthesia. Results: The mean age of our patients was 64.33(SD: 12.085) years; females constituted 73 of them (61.3%) and males 46 (38.7%). Most patients (73) were complaining from the cardiovascular diseases (61.34%). In most patients the onset of the action of the anesthesia was between 10-12 minutes. In 55 patients (46.2%) no extra-drugs were required, and in the rest of patients intravenous mediations were given to relieve anxiety, pain, or both. In 81 patients (68.1%) no intraoperative complications were reported, the most common intraoperative complication was hypotension in 31 patients (26.1%), post-operatively no complications were reported in 86 patients (72%), and hypotension was reported in 12 patients (10.1%), nausea & vomiting in 11 patients (9.2%). The surgeon’s satisfaction was excellent in 73.11% of the surgeries, as was good in 23.53%. Most patients gained the lower limb movement within 2 hours. There was a significant correlation between the need for extra drugs and both comorbid diseases and the development of intraoperative complications (P values 0.022 & 0.000) respectively and no significant correlations with other parameters such as the gender, postoperative complications and the surgeon’s satisfaction (P values 0.707, 0.522, and 0.056) respectively.